Fatores que interferem na duração do aleitamento materno de crianças na Região Metropolitana do Cariri cearense - Aline Muniz Cruz Tavares; Fernanda Ribeiro da Silva; Maria Auxiliadora Macedo Callou; Rejane Ferreira da Silva; Monise Pricila Salviano de Morais; Élida Mara Braga Rocha (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: Exclusive Breastfeeding (EBF) is a fundamental dietary practice for the promotion of maternal and child health. Unfortunately, the rates for EBF in Brazil are still below that recommended by the World Health Organization. Objective: To analyze the factors that interfere in the duration of breastfeeding of children living in the metropolitan region of Cariri, Ceará. Method: Descriptive cross-sectional study, with a quantitative approach, carried out in the Metropolitan Region of Cariri, Ceará. The sample consisted of 177 children between 6 and 23 months of age. The data were collected through questionnaires containing information about the socioeconomic and demographic conditions of the family and child health. Statistical analyses were performed using the software Statistical Package for the Social Sciences, proceeding to the data descriptive analysis, application of the Chi-Square test, Odds Ratios (OR), 95% Confidence Interval (95% CI) and respective values of p were calculated by multinomial logistic regression. Results: The mean EBF length was 4.33 (± 1.98) months, only 38.9% of the evaluated children were exclusively breastfed until 6 months of life. In the multivariate logistic regression analysis, a greater chance of adequate EBF length was verified in families with <1/4 minimum wage (OR: 2.270 95% CI 1.104 - 4.666, p = 0.026). Conclusion: EBF in the municipalities evaluated is still unsatisfactory according to the recommendations recommended by health entities. Low per capita income was the determining factor for the proper practice of EBF in the lives of infants.